Legal and Institutional Obstacles to Growth and Business in Russia - Buckberg, Elaine (Washington, D.C. : International Monetary Fund, 1997)
Although financial stabilization has laid the foundation for growth, structural reform of the economy will determine whether Russia achieves sustained medium-term growth. The next step for Russia is to create an institutional and regulatory environment that fosters investment and promotes new private sector activity. This paper examines the most critical reforms for promoting private sector development: reforming the tax system, reducing red tape and bureaucratic corruption, strengthening the judicial system, and improving capital market infrastructure.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet